Effects of an inulin and microcrystalline cellulose hybrid hydrogel on the short-term low temperature storage characteristics of pork sausage models. (May 2023) - Li, Yan; Xu, Zhiqiang; Sun, Jingxin; Zhu, Yinglian
Abstract: Herein, we applied plant-based fibrous ingredients to reduced-fat emulsifying pork sausage models to partially achieve improvable storage quality and wellness purpose. The hybrid hydrogel comprised of long-chain inulin, microcrystalline cellulose (IMC), and glucolactone was incorporated into 90% of minced lean pork to constitute 5% and 10% respectively of total mass of lean, IMC gel, and pork backfat, corresponding to the addition of pork backfat as 5% and 0%. After 20-day storage at 4 °C, compared to control without IMC gel, addition of IMC gel evidently reinforces hardness, chewiness, and water holding capacity in the matrices of sausage models. Furthermore, IMC gel causes noticeable increases in metmyoglobin content and thiobarbituric acid reactive substance (TBARS) value, and a decrease in peroxide value (POV), implying deep lipid oxidation and fostering the oxidation stability. IMC gel brings about distinct decreases of α-helix conformation and aliphatic groups (methyl and methylene), and evident increases of β-fold conformation and gauche-gauche-gauche disulfide bond conformation. Dynamic rheology shows that IMC gel combined with backfat (5%:5%) is beneficial to the maintenance of higher viscoelasticity than that (10%:0%). Scanning electron microscopy similarly displays that the sausage model using the formulation (5%:5%) possesses more promising appearances of emulsion-filled composite crosslinking networks than the control (0%:10%) and the sausage model using the formulation (10%:0%). The findings demonstrated that IMC gel as a fat replacer may offer potential advantages in upscaling healthier reduced-fat sausage quality. Graphical abstract: Image 1 Highlights: An inulin and MCC hybrid hydrogel was used to reformulate reduced-fat sausage models. IMC gel improves hardness, chewiness, and water-holding capacity. IMC gel increases metmyoglobin content and TBARS value and decreases POV. IMC gel fosters the conversion of α-helix into β-fold, as well as instable TGT into stable GGG . IMC gel combined with fat maintains higher rheological viscoelasticity.